왜곡이 있는 경우 개방경제와 폐쇄경제의 통화정책 비교: 간단한 변환과 적용 - 정규철 (13565, 2014)
This paper compares the monetary policy problem in open economies with that in closed economies. It is found that the monetary policy problems in open and closed economies are isomorphic even in the presence of distortions in a steady state and hence the